The effect of work-hardening and thermal annealing on the early stages of the uranium-hydrogen corrosion reaction. (February 2018) - Banos, A.; Jones, C.P.; Scott, T.B.
Highlights: Distinct differences in (early) H2 corrosion of U due to differences in the level of induced strain in the metal. Mass of hydride decreases from the work-hardened to an as-cast and then a thermally annealed metal surface. Damage per hydride growth decreases from the work-hardened to the as-cast and finally the thermally annealed surface. Vacuum annealing of uranium resulted in a reduction of UH3 nucleation per unit area. Cold work-hardening significantly altered the (early) H2 corrosion behaviour. Abstract: The characteristics of hydride formation on metallic U at the early stages were investigated for three differently treated samples. The first sample reacted in its as-received state, the second was thermally annealed and the third sample underwent cold work-hardening prior to reaction with deuterium. From the analysis, the vacuum heat-treated sample was found to be more resilient to hydriding at the nucleation and growth stage, exhibiting a reduced number of nucleation points when compared to the as-cast uranium. The work-hardened sample was observed to be more susceptible to H2 corrosion, displaying very dissimilar hydriding behaviour when compared to the other.